Investigating Cloud Computing Adoption Reluctance Among Small Financial, Healthcare, and Leisure Industries in the United States - Talib, Ayman; Shaban, Jamal (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2016)
This study aims to explore the factors that hinder small organizations in the United States from adopting cloud computing. The study focused on extending the Technology Acceptance Model (TAM) to include the external variables that can have an impact on small organizations’ decisions when adopting the cloud technology. This study focused on small organizations from three service sectors, financial, health care and leisure. An Internet based survey was sent out to 131 participants who were conveniently sampled with an attempt to collect information about their concerns of the cloud technology. The findings indicate that small organizations are not adopting the cloud technology due to five main factors: security, compliance, service level agreement, business continuity and contract lock-in.